Sedimentation and Diffusion in Nanofluids in Rotating Systems of Metallic Friction Elements of Brake (Part I) - Janahmadov, A.Kh.; Volchenko N.А.; Javadov, M.Y.; Nischuk, V.V.; Andreichikov, Ye.Yu.; Skrypnyk, V.S.; Zhuravlev, D.Yu. (Herald of Azerbaijan Engineering Academy, 2023)
According to the principles of nonequilibrium thermodynamics, it is necessary to study the processes of heat generation in friction pairs and the local nature of its removal from the inner surface of the brake pulley rim. Such means are briquettes made of nanoparticles and forming capillary structures resting in metal frames. The latter are installed in three rows in wide circular grooves on the inner surface of the pulley rim, to which the fluid chamber is attached. The interaction of the latter with the nanocapillary structure in briquettes is described. The connection between sedimentation and diffusion in a nanofluid was carried out by means of the intensity of the entropy source caused by the frictional interaction of metal-polymer friction pairs. To assess sedimentation, the gradient theory was applied to pressure, velocity, partial and specific volume, mass and molar concentration, as well as the determination of the sedimentation coefficient. The diffusion of nanoparticles was characterized by the coefficient and its mobility in the liquid. Selection by molecular weight of various materials of nanoparticles was made. The results of experimental studies on a model band-shoe brake are presented and the cooling efficiency is established.